2017
DOI: 10.1287/mnsc.2016.2555
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Regret and Product Innovation

Abstract: When a firm introduces a product with new features, some consumers may find it difficult to assess their valuations for these new attributes. Their purchase decisions made under such uncertainty may lead to postpurchase regret. It has been experimentally shown that consumers may anticipate their potential postpurchase regret and make their current choices to mitigate or minimize it. That is, a consumer’s anticipated regret can significantly impact his purchase decision. Given the trend that firms in various ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 43 publications
3
62
0
2
Order By: Relevance
“…More recent studies have investigated the role of regret and risk taking and product innovations and product technology management (Jiang, Narasimhan, & Turut, ; Loch, ). Wuttke, Donohue, and Siemsen () investigate the main characteristics of innovation projects contributing to a supplier's acceptance of innovation and new product development through a controlled lab experiment.…”
Section: Literature Classification Based On Operations Contextsmentioning
confidence: 99%
“…More recent studies have investigated the role of regret and risk taking and product innovations and product technology management (Jiang, Narasimhan, & Turut, ; Loch, ). Wuttke, Donohue, and Siemsen () investigate the main characteristics of innovation projects contributing to a supplier's acceptance of innovation and new product development through a controlled lab experiment.…”
Section: Literature Classification Based On Operations Contextsmentioning
confidence: 99%
“…The presence of regret is known to negatively influence user satisfaction, repurchase intention, and the continuance of using a particular service (Kaur et al 2016). Even the anticipation of regret can influence user behavior: Users will adjust their choices in advance in order to mitigate or minimize the experience of regret, which consequently factors into users' final purchasing decisions (Greenleaf 2004;Jiang et al 2016). Similarly, studies have shown that incorporating regret in the utility function can explain some well-known behavioral anomalies, such as the Allais Paradox, the coexistence of insurance and gambling, the fact that people tend to be risk averse in the domain of gains and risk-loving in the domain of losses, probabilistic insurance, and preference reversals (see Engelbrecht-Wiggans and Katok 2008).…”
Section: Related Studies On Regretmentioning
confidence: 99%
“…For instance, regret has been shown to depend on the specific information that is provided to the winners or losers of an auction (Engelbrecht-Wiggans 1989). Recently, regret has also been shown to depend on consumers' uncertainty about either the product's objective attributes (e.g., a product's quality) or the consumer's own preferences for a product's known attributes (Jiang et al 2016). Taking stock of these studies, our study seeks to better understand the antecedents of regret by enquiring into the effects of auction design associated with different degrees of bid disclosure on post-purchase regret.…”
Section: Related Studies On Regretmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, this information can be represented through linguistic two-tuples [19,20], interval-valued rough random variables [17], or hesitant fuzzy linguistic terms [18,21]. In addition, regret theory has an important role in decision theory, such as in the dynamic location problem [22], enterprise production, and marketing strategy [23].…”
Section: Introductionmentioning
confidence: 99%